Mediation Skill Improvement in Special Branch Leader of ‘Aisyiyah in Malaysia for Effective Dispute Resolution - Cahyani, Tinuk Dwi; Nasyithah, Nita (Jurnal Dedikasi Hukum, 2024)
Mediation Skill Improvement in Special Branch of ‘Aisyiyah in Malaysia for Effective Dispute Resolution Law counsel for mediators aims to resolve legal issue faced by the cadres and Indonesian citizens who stay in Malaysia. In contrast, the heads of ‘Aisyiyah Special Branch Leaders (PCIA) do not possess a particular skill that can be used as an alternative in resolving disputes out of court, which is mediation. Mediation is used to bring bargaining value closer to an agreement. Mediators tend to be more focused on the problems or the positions claimed by parties. The counseling method is implemented by arrangement, mediator’s role and function review, tasks division, and dialogue session. During this agenda, all participants participate in experience simulations, which are carried out by each group. The role of the third party, in this case, the mediator, in completing the task is to become a middleman between parties resolving disputes. As a middleman’, it means that mediators must position themselves as neutral parties and must choose nobody's side while resolving disputes. Through this law community service, participants deliver their reviews during dialogue sessions, they reveal that there is a significant improvement in understanding concepts of mediation’s key such as the mediator’s role, negotiation technique, and how to constructively overcome legal issues.   Abstrak Peningkatan Keterampilan Mediasi di Pimpinan Cabang Istimewa ‘Aisyiyah Malaysia dalam Penyelesaian Sengketa yang Efektif Penyuluhan hukum bagi mediator ini bertujuan membantu menyelesaikan masalah hukum yang dihadapi oleh para kader dan warga negara Indonesia yang tinggal di Malaysia. Namun disisi lain, para pimpinan di Pimpinan Cabang Istimewa ‘Aisyiyah (PCIA) belum memiliki keahlian khususnya mengenai alternatif penyelesaian sengketa diluar pengadilan, yaitu mediasi. Mediasi dimaksudkan guna mendekatkan perbedaan nilai tawar atas suatu kesepakatan. Mediator hanya terfokus pada permasalahan atau posisi yang dinyatakan para pihak. Metode penyuluhan ini dilaksanakan dengan persiapan, pemaparan peran dan fungsi mediator, pembagian tugas, hingga tanya jawab. Dalam agenda ini seluruh peserta menyaksikan simulasi mediasi yang dilakukan setiap kelompok. Peranan pihak ketiga, dalam hal ini sebagai mediator, dalam menjalankan tugasnya yaitu menengahi para pihak dalam menyelesaikan sengketa. “Berada di tengah” memiliki arti juga bahwa mediator harus berposisi sebagai pihak yang netral atau tidak memihak dalam menyelesaiakan sengketa. Melalui pengabdian hukum ini, peserta memberikan pesan-kesan dalam sesi tanya jawab bahwa terjadi peningkatan pemahaman yang signifikan tentang konsep-konsep kunci mediasi, seperti peran mediator, teknik negosiasi, dan cara mengatasi konflik secara konstruktif.